USM, MPSP WORK WITH JAPANESE PARTNERS TO RESTORE MARKET - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 January 2016 – Universiti Sains Malaysia (USM) is working together with three partners from Japan, namely Japan International Cooperation Agency (JICA), Yokohama City University (YCU) and the City of Yokohama (CY) as well as the Seberang Perai Municipal Council (Majlis Perbandaran Seberang Perai/MPSP) on a project to restore the old market in Bukit Mertajam, Pulau Pinang.